Ir(iii)-catalyzed quadruple C–H activation of N-arylimidazolium and diaryliodonium salts: facile access to polysubstituted imidazo[1, 2-f]phenanthridiniums. Issue 50 (1st June 2022) - Liu, Zheng; Li, Qian; Yang, Chengyong; Zheng, Xuesong; Wu, Di; Gao, Ge; Lan, Jingbo
Abstract : N-heterocyclic carbene-directed Ir(iii )-catalyzed cascade C–H arylation/annulation of N -arylimidazolium with diaryliodonium salts has been accomplished for the first time via a quadruple C–H activation strategy. Abstract : Herein, N-heterocyclic carbene-directed Ir(iii )-catalyzed cascade C–H arylation/annulation of N -arylimidazolium with diaryliodonium salts has been accomplished for the first time via a quadruple C–H activation strategy to construct imidazo[1, 2- f ]phenanthridinium structures. This protocol overcomes the compatibility of three kinds of different C–H activations with high catalytic efficiency, which allows ortho -unhindered N -arylimidazoliums to undergo a diarylation/annulation reaction, affording a variety of polysubstituted imidazo[1, 2- f ]phenanthridiniums. Neutral imidazo[1, 2- f ]phenanthridines are also prepared via a demethylation reaction of imidazo[1, 2- f ]phenanthridiniums.